Rooting of Tineke and Natal Briar rose stem cuttings in different substrates - Giovana Ritter; Ellen Toews Doll Hojo; Fabíola Villa; Daniel Fernandes da Silva (Ciência Rural, 2018)
ABSTRACT: The commercial propagation of rose bushes is carried out asexually by the cutting method. The genetic material and the substrate are factors that interfere in the rhizogenic process of the cuttings. Thus, the aim of this work was to evaluate the effect of the substrate on the rooting of cuttings of two hybrid rose bushes. Floriferous branches of matrix plants were cut at the apex and at the base, approximately 8cm long and with two buds, and the basal leaf was removed. The experimental design was completely randomized, in a 2 × 3 factorial scheme (two cultivars, Tineke and Natal Briar × three substrates, carbonized rice husk, coconut fiber and TN Gold®) containing four replicates of 15 cuttings per replicate. The base of the cuttings was immersed for five seconds in IBA 2000mg L-1 solution (indole butyric acid). The cuttings were placed in trays with 24 cells previously filled with substrate and deposited on the floor in a transparent plastic tunnel, built inside a stove. After the 50-day experiment, rootstocks (%), sprouts (%) and dead (%), root length (cm), fresh and dry shoot biomass and roots (g) were evaluated. The rooting percentage of the Natal Briar cultivar was 75%, thus superior to the Tineke cultivar, which had a rooting percentage of 39%. The best substrates for the Tineke and Natal Briar rose cuttings are CAC and coconut fiber, which provided rooting percentages of 81% and 67% of the cuttings, respectively.